Psychological empowerment and organizational citizenship behavior in the information communications and technology (ICT) sector: A moderated- mediation model - Ahmad Almohtaseb; Maha Shehadeh; Jehad Aldehayyat (Cogent Business & Management, 2023)
This study aimed to examine the influence of psychological empowerment on job crafting. Moreover, it analyzed the relationship between job crafting and organizational citizenship behavior. In addition, conscientiousness was considered as a moderator between psychological empowerment and job crafting. Whereas the mediation effect of job crafting was examined among psychological empowerment and organizational citizenship behavior. The data were gathered from the ICTs of Jordan and AMOS was used for analysis. The results highlighted that psychological empowerment can influence job crafting, which can lead to organizational citizenship behavior. Therefore, job crafting can significantly mediate the relationship between psychological empowerment and organizational citizenship behavior. In addition, the findings revealed that conscientiousness being an important personality trait can moderate the relationship between psychological empowerment and job crafting. This research can be considered as a guideline for researchers and practitioners focusing on job crafting and organizational citizenship behavior. The focus of this research is merely on the employees of ICTs and it has considered only one personality trait i.e. conscientiousness. Therefore, future studies can emphasize any other sector and include other personality traits as moderators.
Keywords: 650; Conscientiousness; Icts; Job Crafting; Organizational Citizenship Behavior; Psychological Empowerment